Netflix, Wasp Network and the Cuban exile settled in Miami - Martínez, Rafael Ángel Salazar; Portal Moreno, Rayza (Technium Social Sciences Journal, 2021)
Since its premiere, “Wasp Network” film has been object of intense activism against the Cuban exiles settled in Miami. In that sense, this paper aims to determine the incidence of this activism on the film’s trajectory on Netflix. Document review and content analysis are used as techniques. The main finding shows that, in face of pretense that film was not seen, there was an opposite impact, with particular emphasis on the Cuban community itself in United States and, to a lesser extent, in Spain and Latin American countries.